Using High Fidelity Simulation to increase a physiotherapist's self assessed competence and confidence when treating critically ill patients - a preliminary investigation - Khoo, Lin Shan Melissa (Auckland University of Technology, 2011)
High Fidelity Simulation (HFS) has been increasingly incorporated into health care education as this form of education has been shown to develop both the non technical and technical skills of healthcare professionals, which potentially results in increases in the standards of patient care. To date, there have been no studies to demonstrate this effect in the field of cardiorespiratory physiotherapy. Similarly, there has been scant literature to guide the design and development of a physiotherapy HFS programme in a hospital setting. This study, conducted in a tertiary hospital in Singapore, involved the design and implementation of an evidence based physiotherapy HFS programme, which incorporated the physiotherapy assessment and treatment of critically ill patients. The changes in self assessed competence and confidence levels of the ten physiotherapists who participated in the HFS programme were measured pre and post intervention. The results of this study indicated that a one hour physiotherapy HFS programme significantly increased the participants’ self assessed competence when treating critically ill patients in HFS case scenarios. It is suggested that further large or multi-institutional studies using externally validated measuring instruments are needed to provide more evidence that the participation in a HFS programme can significantly increase physiotherapist’s self assessed competence and confidence levels when treating a critically ill patient.
Keywords: HFS; Confidence; Competence; High Fidelity Simulation